Designer Bloch plasmon polariton dispersion in grating-coupled hyperbolic metamaterials - Nicolò Maccaferri; Tommi Isoniemi; Michael Hinczewski; Marzia Iarossi; Giuseppe Strangi; Francesco De Angelis (APL Photonics, 2020)
Hyperbolic metamaterials (HMMs) are anisotropic optical materials supporting highly confined propagating electromagnetic modes. However, it is challenging to tailor and excite these modes at optical frequencies by prism coupling because of the unavailability of high refractive index prisms for matching the momentum between the incident light and the guided modes. Here, we report on the mechanism of excitation of high-index Bloch plasmon polariton modes with sub-diffraction spatial confinement using a meta-grating, which is a combined structure of a metallic diffraction grating and a type II HMM. We show how a one-dimensional plasmonic grating without any mode in the infrared spectral range, if coupled to an HMM supporting high-index modes, can efficiently enable the excitation of these modes via coupling to far-field radiation. Our theoretical predictions are confirmed by experimental reflection measurements as a function of angle of incidence and excitation wavelength. We introduce design principles to achieve a full control of high-index modes in meta-gratings, thus enabling a better understanding of light–matter interaction in this type of hybrid structure. The exploitation of the spectral response of these modes can find applications in bio-chemical sensing, integrated optics, and optical sub-wavelength imaging.